Experience of family of children’s hospitalization at the ICU. - Martins Faria Faddul Alves, Maria Virginia; Gonzaga Cordeiro, Juliana; Bronzato Luppi, Claudia Helena; Trevizani Nitsche, Maria José; Leite Rosa Olbrich, Sandra Regina (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> Objective. To describe the experience of family members as a result of children’s hospitalization at the Intensive Care Unit (ICU). Methodology. Descriptive and cross-sectional study. A structured interview was held with 20 relatives of patients hospitalized at two clinics of the Botucatu Medical School at Universidade Estadual Paulista “Júlio de Mesquita Filho”. Information was collected between July and September 2010. Results. The main characteristics of the participating relatives were: 80% mothers of the children; 70% low education level and 70% married. Sixty percent of the children were hospitalized at the ICU for the first time. Eighty percent of the interviewees believe that the children’s behavior changes inside the unit and 85% consider that visiting hours are sufficient. The predominant negative feelings are fear (50%) and insecurity (20%), while the predominant positive feelings are hope (50%) and the expectation of discharge (25%). The professional who most supported the relatives was the nurse (35%). Conclusion. The family members’ experience as a result of the children’s hospitalization at the ICU involves positive and negative aspects, which also affect the child’s behavior at the unit. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->